Product & service innovation and organizational performance: a comparative study of government and private sectors / Amariah Hanum Hussin - Hussin, Amariah Hanum (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Innovative capabilities refer to an organization’s ability to recognize and transform new ideas into improved products or services for the organization’s benefit (Mendoza-Silva, 2020). In this context, innovation is crucial as it drives economic growth, competitiveness, sustainability, performance improvement, and competitive edge in the market (Buenechea-Elberdin et al., 2018; Omar et al., 2017). Innovation may enhance the existing product quality and is able to introduce new products to the customer. At the same time, it also allows cooperatives to gain more opportunities for expanding their current businesses. It becomes one of the critical factors of a firm’s competitiveness, suggesting that the more a firm is innovative, the more productive it is, and the better the overall firm performance Aljuboori et al. (2021). In contrast, low innovation performance will accordingly lead to lower profitability and customer loyalty (Hanifah H et al 2020). Research suggests that innovation performance is a product of competitive advantage derived from utilizing internal and external resources. For instance, combining internal and external resources can enhance innovative performance and lead to increased performance (Ferraris et al., 2017). Therefore, all organizations need to adapt with new norms and technology, amidst Covid-19 pandemic regardless government or private sector as the impact of Covid-19 pandemic hits every aspect of life.